Dynamic Mechanical Thermal Analysis (DMTA) of Thermoplastic Natural Rubber (TPNR) Barium Ferrite (bafe12o19) Composites - S Hamdan; D.M.A Hasihim; M Yusop (ASEAN Journal on Science and Technology for Development, 2004)
filled with 0-6 volume percentage of barium ferrite was performed using a Polymer Laboratory- Dynamic Mechanical Thermal Analyser (PL-DMTA) over a range of temperature from -100 to 100°C at 10hz. The results showed that the storage modulus (E') of the composites below the transition temperature increase with filler content up to ~3-4 volume percentage. Incorporation of the filler does not change the matrix glass transition that occurs around -40°C but the damping curve becomes broader with increasing filler content. The addition of filler in the compositedoes not affect the glass transition and melting temperature. The blend of TPNR and barium ferrite powder is only a physical mixture that does not act chemically.